Cryptosporidium spp. Infection in Solid Organ Transplantation: The Nationwide "TRANSCRYPTO" Study. Issue 4 (April 2017) - Lanternier, Fanny; Amazzough, Karima; Favennec, Loic; Mamzer-Bruneel, Marie-France; Abdoul, Hendy; Tourret, Jérome; Decramer, Stéphane; Zuber, Julien; Scemla, Anne; Legendre, Christophe; Lortholary, Olivier; Bougnoux, Marie-Elisabeth
Abstract : Background: Diarrhea is a frequent complication of solid organ transplantation. Cryptosporidiosis is classically reported in patients with acquired immunodeficiency syndrome and emerged as a cause of persistent diarrhea in solid organ transplant patients. Methods: Through the ANOFEL Cryptosporidium National Network and the French Transplantation Society, we collected all cryptosporidiosis cases identified in solid organ transplanted patients between 2006 and 2010 in France. Results: We reported 47 solid organ transplant recipients (41 kidneys) with cryptosporidiosis, mostly men (68%), with a median age of 52 (6-70) years old. Five patients had additional immunodepression favoring cryptosporidiosis (CD40 ligand deficiency [n = 1], human immunodeficiency virus infection [n = 4]). Cryptosporidiosis occurred at a median time of 3.4 (0-19.8) years posttransplant. Exposure to environmental risk factors was found before infection onset in 18 patients. Time between first symptoms and diagnosis was 10 (2-110) days. Four patients had associated extraintestinal location (biliary tract [n = 3] and lung [n = 1]). Thirty-five patients received specific therapy against cryptosporidiosis ie nitozoxanide, 25 in monotherapy, and 10 in association with azithromycin, 13 in association with immunosuppression (IS) reduction. Four patients were cured with IS treatment tapering only. The others patients had neither IS reduction nor specific therapy against cryptosporidiosis. Cryptosporidiosis was complicated by renal failure in 15 patients. Symptoms resolved after a median of 10 days of treatment. Six patients relapsed and 3 died, 1 with evolutive infection. Conclusions: Cryptosporidiosis is a late posttransplant infection that disseminated to biliar duct or lung in 9% of patients. When limited to digestive tract, infection may resolve without IS reduction. Abstract : This French multicenter study is the largest study of Cryptosporidium infection in transplant patients outside of endemic areas like India, and shows that it can be eradicated without immunosuppressive reduction in many patients.